Counselor’s Experience in Conducting Online Psychological Services - Mohd Shahrul, Kamaruddin; Aini Azeqa, Ma’rof; Chin, Chew Lin (Institute for Learning Innovation and Counseling, Indonesia, 2024)
The outbreak of the 2019 Coronavirus disease (Covid-19) that hit worldwide has a direct impact on public health not only in terms of physical and mental well-being but also in terms of psychological, social, and emotional well-being. The use of online psychological support is a method that has been used to ensure the community who has contact status gets the guidance and outreach purposes, especially for the purpose of social and emotional support during the outbreak of Covid-19. This approach is seen as an alternative to ensure that the psychology of the community is in a calm and stable state by alleviating the annoyances faced by the community. The resilience of the community plays an important role in adapting to the new norms of life in difficult conditions. Therefore, there are also issues and challenges faced by counselors in helping the community to continue the new norms of life in the face of the Covid-19 pandemic. Therefore, the implications and discussions from the counselor's experience are also stated as well as further research suggestions are also suggested for further research by the researcher.